Encyclopedia & dictionary of medicine, nursing, & allied health (Philadelphia, 2003)
Encyclopedia and dictionary serves as a current, comprehensive vocabulary source for the health sciences. Includes 3,900 new entries, with archaic and obsolete terms deleted. The latest changes for diagnosis-related groups, nursing diagnoses, and other key nursing taxonomies are included. Revised tables and illustrations.
Keywords: Medicine,Nursing,Allied health personnel,Thuốc uống,Điều dưỡng